COMPREHENSIVE ANALYSIS OF CLINICAL TRIALS IN PAKISTAN FROM SEPTEMBER 1992 TO FEBRUARY 2019 - Siddique, Amna; Zafar, Amara; Irfan, Tooba (Journal of Ayub Medical College Abbottabad, 2022)
Background: Clinical trials are conducted to evaluate interventions (drugs, medical devices, surgical methods and radiation treatment) for treating diseases or conditions. They may also be done to prevent the development or prevent recurrence or determining risk factors. We wanted to review the current status of clinical trials in Pakistan. Methods: On searching ClinicalTrials.gov, registered clinical trials conducted in Pakistan from September 1992 to February 2019 were reviewed. The analysis evaluated the characteristics of the clinical studies including the type of intervention, geographic distribution of studies, anticipated enrolment and number of participants, blinding, allocation status, lead sponsors, age group, study type, recruitment status, gender, study results, study phase, primary purpose and subject distribution. The results were tabulated with frequencies and percentages provided by category. Results: There were 508 registered clinical trials conducted in Pakistan from September 1992 to February 2019. Interventional clinical trials were conducted more often than observational trials (77.2% and 22.8% respectively), with drugs (41.4%) as the most common intervention. The majority of registered trials had participants ranging between 101-1000 (47.2%) with most having no blinding in their methodology (34.1%). Most of the trials conducted were randomized (66.5%) while few (5.3%) were non-randomized. Among the sponsor categories, 66.5% of the trials belong to the ’˜Other’ (non-governmental, non-industry) category. Although 59.6% of the registered trials have been completed, most of them (91.3%) did not report their results. Treatment intervention trials in Internal Medicine were the most common primary purpose. An increasing trend in the frequency of clinical trials was also evident. Conclusion: The number of clinical trials in Pakistan showed an increasing trend over the time period studied, which may reflect on the general outlook of clinical research in the country. Most clinical trials were sponsored by universities, hospitals and non-profit organizations but less than 10% of studies reported results